CASE REPORT: NASOPHARYNGEAL CARCINOMA IN PREGNANCY - Sugeng Santoso (TALENTA PUBLISHER, 2020)
Abstract Introduction: Nasopharyngeal carcinoma in pregnancy is a rare case, a dilemma in its management. This condition has a significant negative effect on pregnancy, given risk of premature birth, fetal defects and abortion. Case Report: 23-year-old woman with 13 weeks gestation age comes with swelling in both necks accompanied by nosebleeds. On nasoendoscopic examination, there was a mass at nasopharynx. Histopathological examination results a nasopharyngeal squamous cell carcinoma. Conclusion: The management of nasopharyngeal carcinoma in pregnancy is very complex, need for extensive multidisciplinary approach with experienced doctors in their respective fields